Hemorrhagic erucism due to Lonomia spp. in Peru – A call for action - Edgar A. Ramírez García; Maria José Valentina Canchanya-Olimar; Mariana Rojas del Águila; Nelson Iván Agudelo Higuita; Andrés F. Henao-Martínez; Carlos Franco-Paredes; Luis A. Marcos; Juan C. Celis Salinas; Martín Casapia Morales (Travel Medicine and Infectious Disease)
Envenomation due to exposure to caterpillars is an emerging public health problem. A life-threatening bleeding diathesis has been described in South America after exposure to Lonomia obliqua or L. acheolus. Deforestation, forest degradation, and global warming might increase the frequency of human exposure to these insects. Prompt recognition and administration of antivenom are crucial to ensure a favorable outcome.